2023
DOI: 10.3389/fpubh.2022.1047710
|View full text |Cite
|
Sign up to set email alerts
|

Does self-medication reduce medical expenditure among the middle-aged and elderly population? A four-wave longitudinal study in China

Abstract: IntroductionSelf-medication has a high prevalence in the middle-aged and elderly population in China. Despite the published evidence demonstrating the economic benefits of self-medication, limited research has addressed the relationship between self-medication and individual medical expenditures, especially within the Chinese population. This study examined the effect of self-medication on individual medical expenditures in China and analyzed the heterogeneity between outpatient and inpatient cases.MethodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…From a public health and national burden of disease perspective, suppression of healthcare needs often leads to disease exacerbation, causes augmented disease risk and constraints disease treatment and prevention, which increases the social burden of long-run healthcare [63-64]. In addition, in the individual perspective, studies suggested that The elderly who adopt selfmedication are less likely to use inpatient services, and their hospitalization costs are signi cantly lower [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a public health and national burden of disease perspective, suppression of healthcare needs often leads to disease exacerbation, causes augmented disease risk and constraints disease treatment and prevention, which increases the social burden of long-run healthcare [63-64]. In addition, in the individual perspective, studies suggested that The elderly who adopt selfmedication are less likely to use inpatient services, and their hospitalization costs are signi cantly lower [21].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to urban respondents, rural residents were more likely to consider drug price as a decision factor in purchasing over-thecounter drugs [17]. Proper self-medication can reduce the long-term healthcare burden at the individual and societal level [21][22]. In addition to conventional healthcare resources such as inpatient and outpatient care, self-medication, especially over-the-counter drugs, deserves special attention for rural residents.…”
Section: Introductionmentioning
confidence: 99%
“…From a public health and national burden of disease perspective, suppression of healthcare needs often leads to disease exacerbation, causes augmented disease risk and constraints disease treatment and prevention, which increases the social burden of long-run healthcare [ 64 , 65 ]. In addition, in the individual perspective, studies suggested that the elderly who adopt self-medication are less likely to use inpatient services, and their hospitalization costs are significantly lower [ 21 ]. The economic value of self-medication among the Chinese elderly population is also significant at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to urban respondents, rural residents were more likely to consider drug price as a decision factor in purchasing over-the-counter drugs [ 17 ]. Proper self-medication can reduce the long-term healthcare burden at the individual and societal level [ 21 , 22 ]. In addition to conventional healthcare resources such as inpatient and outpatient care, self-medication, especially over-the-counter drugs, deserves special attention for rural residents.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated an increasingly trend of self-medication among middle-aged and older adults in China and the growing pharmaceutical expenditure that come with it. According to prior study, the popularity of self-medication in this group can be attributed to its cost and time savings ( 31 ).…”
Section: Discussionmentioning
confidence: 99%